Breaking barriers: How transwomen meet their healthcare needs - Millicent Maoto; Burt Davis (AOSIS, 2024)
Background: Transgender women - individuals assigned male at birth but who identify as female - are disproportionately affected by, among others, human immunodeficiency virus (HIV), other sexually transmitted diseases (STIs) and mental health issues. Studies show that transgender women often encounter discrimination and stigma when seeking healthcare from health facilities. Aim: This study assessed the healthcare needs of transgender women, their experiences of the mainstream healthcare system and alternative strategies for navigating the healthcare system. Setting: The study was carried out in the City of Ekurhuleni Metropolitan Council in South Africa's Gauteng province. Methods: A case study design was followed. Participants were purposively selected and included 10 transgender women aged 26-50. Individual semi-structured interviews were conducted over 2 months. Results: Participants expressed a need for hormone replacement therapy, HIV treatment and prevention and treatment for STIs. Experiences of participants within the healthcare system were predominantly negative, with instances of discrimination, stigma and privacy violations being commonplace. Alternative strategies to meet their healthcare needs included the use of self-medication, consulting traditional healers and utilising non-governmental organisations. Conclusion: There is an urgent need for equitable and inclusive health management of transgender women in South Africa. Contribution: This study provided a first look in a South African context into how and to what extent transwomen employ alternative healthcare strategies such as self-medication and utilising non-governmental organisations when faced with mainstream healthcare access barriers. The use of traditional doctors was identified as a novel, alternative strategy used by transwomen to access healthcare and treatment.